PDK2-enhanced glycolysis aggravates fibrosis via IL11 signaling pathway in Graves’ orbitopathy - Peng, Zhiyu; Huang, Rui; Gan, Lu; Wang, Jinghan; Li, Xiaofeng; Ding, Jie; Han, Yinan; Wu, Jihong; Xue, Kang; Guo, Jie; Zhang, Rui; Qian, Jiang; et al. (Frontiers in Immunology, 2025)
ObjectivesTransforming growth factor β1 (TGFβ1)-interleukin 11 (IL11) is a newly found critical signaling pathway in fibrotic diseases such as Graves’ orbitopathy (GO). It has now been confirmed that enhanced glycolysis plays a key role in the pathogenesis of GO. However, little is known about the relationship between glycolysis and IL11-mediated fibrosis in GO. This study aimed to identify the relationship between glycolysis and TGFβ1-IL11 signaling pathway and investigate the role of IL11 in glycolysis-facilitated fibrosis in GO.MethodsOrbital connective tissues were collected from GO and control patients. Primary orbital fibroblasts (OFs) were cultured from clinical tissues. Patient-derived xenografts were established via intraorbital transplantation of GO orbital tissue in humanized NCG mice. Protein levels were measured using Capillary Western Immunoassay (WES). Small interfering RNA (siRNA) was used to construct transfected OF strains. Lactate production was measured to assess glycolysis status. Animal models were assessed by T2-weighted magnetic resonance (MR) scan. Immunohistochemistry staining was applied to patients’ orbital connective tissues.ResultsOrbital connective tissues were collected from GO patients. Immunohistochemical (IHC) staining of GO tissues revealed the phenomenon of pyruvate dehydrogenase kinase 2 (PDK2)-enhanced glycolysis and upregulated IL11-IL11Rα pathway. In vitro experiments showed successful induction of fibrosis of patient-derived orbital fat/connective tissues, which could be alleviated by dichloroacetic acid (DCA). MRI images and analysis of hematoxylin and eosin (HE) and Masson-stained section demonstrated enhanced glycolysis in GO, facilitating fibrosis of the orbital tissue. Targeting PDK2 decreased IL11 expression to suppress fibrosis. In vivo experiment confirmed anti-fibrotic effect of inhibition of glycolysis.ConclusionsPDK2-enhanced glycolysis exacerbates fibrosis via IL11-IL11Rα signaling pathway, shedding light on a potential therapeutic role of metabolic modulators such as DCA in GO treatment.